2006
DOI: 10.1093/carcin/bgl148
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal glutathione transferase 1 in anticancer drug resistance

Abstract: Glutathione transferases (GSTs) are often upregulated in tumors and have been suggested to play an important role in multiple drug resistance in cancer chemotherapy. As a consequence GST-dependent pro-drugs and inhibitors are being developed. Little is known, however, on the potential role of membrane-bound GSTs in drug resistance despite the fact that detoxication of cytostatic drugs and upregulation in tumors has been demonstrated. Therefore, we have studied the involvement of membrane-bound microsomal GST1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 32 publications
2
55
0
Order By: Relevance
“…Their results revealed that high expression of MGST1 is significantly associated with DOX-resistance in patients with Ewing sarcoma during chemotherapy. It was reported that several anticancer drugs were definitely substrates for MGSTs, including melphalan and chlorambucil (CMB) (Johansson et al, 2007), and these drugs can activate MGST by reacting with Cys49 in MGST, thus facilitating its conjugation with GSH. Transporters, especially MRP1 and MRP2, show higher transport velocities (V max values) for the exertion of GSH-conjugated drug, which decreases the concentration of them in cancer cells and results in acquired drug resistance.…”
Section: Gstsmentioning
confidence: 99%
“…Their results revealed that high expression of MGST1 is significantly associated with DOX-resistance in patients with Ewing sarcoma during chemotherapy. It was reported that several anticancer drugs were definitely substrates for MGSTs, including melphalan and chlorambucil (CMB) (Johansson et al, 2007), and these drugs can activate MGST by reacting with Cys49 in MGST, thus facilitating its conjugation with GSH. Transporters, especially MRP1 and MRP2, show higher transport velocities (V max values) for the exertion of GSH-conjugated drug, which decreases the concentration of them in cancer cells and results in acquired drug resistance.…”
Section: Gstsmentioning
confidence: 99%
“…Our result showed a significant increased(p<0.001) activity of GSTs in stage-III (received chemotherapy) than stage-II patients (TABLE 3).Many studies also showed progressive increase of GSTs with advancing cancer and has been associated with poor prognosis and development of drug resistance [11][12][13].K.Johansson et al [13] reported GSTs protect the cells from lipid peroxidation and H2O2which is increased by cisplastin, a chemotherapeutic drug .Our results show the association of serum GST and chemotherapy in oesophagus cancer.…”
Section: Discussionmentioning
confidence: 68%
“…Expression of microsomal glutathione S-transferase (MGST) has been shown to confer resistance to cisplatin [22]. In this analysis, expression of MGST1 [224918_x_at] increased with passage in several cell lines such as LOX IMVI and NCI-H226.…”
Section: Resultsmentioning
confidence: 96%